Horner's syndrome following single lung transplantation. Issue 1 (28th November 2019) - Mohammad, Sanna; Loebe, Matthias; Grant, April A.; Vianna, Rodrigo; Brozzi, Nicolas; Ghodsizad, Ali
Abstract: Lung transplantation have significantly improved quality of life in patients with end stage respiratory failure, however use of lifelong immunosuppressive therapy and development of bronchiolitis obliterans reflects in a 5‐year survival is less the 60%. Ophthalmic complications following lung transplantation are uncommon. Some cases of infectious and malignant ophthalmic complications have been described previously. Here we describe a case of Horner's syndrome following single lung transplantation.